2013
DOI: 10.18052/www.scipress.com/ilshs.19.183
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of In-Service Training Courses on the Teacher’s Attitude and Performance

Abstract: The present article reports on a research designed to examine the effect of teachers in-service training programmes on their attitude and performance. The study was conducted on 100 teacher's trainees in 6 th Education district of Tehran. An attitude questionnaire was used once at the beginning and once at the end of the training course to check the participants' attitude change. The teacher's performance was then observed using an observation checklist. A stimulated recall interview was conducted to check the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The finding of the current study, therefore, was that teachers' self-efficacy can be enhanced by capacity-building programs involving in-service and counselling services. This was similar to [27,28,29,30,31,32] and [33] which had found that capacity-building programs including in-service training and workplace counselling services enhanced workers self-efficacy.…”
Section: On Orientation Through Guidance and Counselling A Teacher Asupporting
confidence: 89%
See 2 more Smart Citations
“…The finding of the current study, therefore, was that teachers' self-efficacy can be enhanced by capacity-building programs involving in-service and counselling services. This was similar to [27,28,29,30,31,32] and [33] which had found that capacity-building programs including in-service training and workplace counselling services enhanced workers self-efficacy.…”
Section: On Orientation Through Guidance and Counselling A Teacher Asupporting
confidence: 89%
“…Consequently [31] investigated the influence of in-service training courses on the teacher's attitude and performance in Iran. The study collected data from 100 teacher's trainees using an attitude questionnaire, checklist and interview.…”
Section: Influence Of Capacity Building Programs On Teachers' Self-efmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the ways for teachers to improve one's competency is to take teacher education courses. Pre-service teacher education and in-service training can play an important role in strengthening teachers' competency [15][16][17][18][19][20]. While teachers' experiences of taking ESD courses in their pre-service teacher education and in their in-service training on ESD may have differential effects on perceived barriers, researchers have not systematically explored whether teachers' experiences of taking ESD courses in their pre-service teacher education and in their in-service training on ESD has an influence or not.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of knowledge, changes in beliefs, gaining skills, developing new attitudes and dispositions (Shahmohammadi, 2014). Ur (1997) colleges or universities".…”
Section: Teacher Education Teacher Training Teacher Developmentmentioning
confidence: 99%